Penggunaan Sistem Keuangan Berbasis Ms. Accesss Dalam Meningkatkan Kualitas Pengelolaan Keuangan UKM Keripik Pisang “Ramesta” - Arif Rizki Fadhillah; Dadang Hermawan (JASTEN (Jurnal Aplikasi Sains Teknologi Nasional), 2021)
A computer-based financial management system is an urgent matter, so that it can help SMEs in running a business with easy and good financial management. One of them is UKM Ramesta, which still uses traditional management systems, so that they do not yet have a financial management system that meets accounting standards. Based on the problems faced by UKM Ramesta, it is necessary to provide training for UKM partners on financial management based on Microsoft Access using the Cashflow Simplebook software. The purpose of this activity is for SMEs to experience increased performance and business competitiveness. Implementation methods in solving problems with UKM Ramesta partners, including: problem identification, problem solution, discussion of the Ramesta UKM implementation team and partners, training on Microsoft Access-based SME financial management systems, evaluating the use of simplebook cashflow software for SME financial management. The conclusion of this activity is to increase the ability and knowledge of UKM Ramesta partners in managing the financial system, the use of the Cashflow Simplebook application helps UKM Ramesta in preparing better financial reports.